Fundamental differences between natural antibodies and polyreactive immunoglobulins - S. A. Bobrovnik; M. A. Demchenko; S. V. Komisarenko (The Ukrainian Biochemical Journal, 2015)
A problem of similarity and differences between so-called polyreactive immunoglobulins (PRIGs) and natural antibodies (NAbs), capable of cross-reacting with some structurally dissimilar antigens, has been considered. The analysis of mechanisms of an unspecific interaction between PRIGs or NAbs and antigens evidences for the fact that essential differences exist between these substances. These differences permit classifying the abovementioned substances as different types of immunoglobulin molecules. The major difference between PRIGs and NAbs may include both the mechanisms of the above mentioned immunoglobulin molecules binding to antigens and their interaction affinity, as well as an absolutely different influence of some low-molecular substances on the efficiency of the interaction with antigens. Relying on the obtained data it can be assumed that, since PRIGs and NAbs have fundamental differences, they may perform not only similar but also different functions of the immune system.